Wave energy converter with floating-point absorber and catenary mooring: dynamic coupling analysis - Zhang, Dapeng; Zhao, Bowen; Jiang, Haoyu (Frontiers in Marine Science, 2024)
Mooring design for floating wave energy converters (WECs) is crucial for station maintaining, efficient power collection, and economic concerns. In order to study the dynamic response of the floating-point absorber under the coupling action of the catenary in regular waves, this research presents the numerical modeling of the floating-point absorber alone with a catenary mooring system. Hydrodynamic behavior of the floating-point absorber is analyzed with respect to wave height, wave period, and current velocity. From the computational fluid dynamics (CFD) results, it can be deduced that the wave height has a much more pronounced impact on the longitudinal motion properties of WEC, such as the longitudinal force and the surge motion, and essentially no impact on the vertical force and the heave motion. The dynamic performance of the WEC under small wave periods are quite different from those under large wave periods. The current velocity also significantly affects the hydrodynamic performance of the WEC. The larger current velocity brings strong nonlinearity for the forces of the WEC. Under the combination of waves and current, the WEC and its mooring system will achieve a dynamic balance.